A scheme for dynamic deployment of bandwidth in opto-electronic switches and agile optical networks - Lu, David Tai-Wei (University of Ottawa (Canada), 2005)
This thesis investigates a novel scheme of Flexible Bandwidth Provision (FBP) in a three-stage packet switch. The proposed switch architecture is a hybrid optics/electronics Clos-like switch. The electronics domain is used as a memory technology, and the photonics domain is used as a communication technology. The architecture and method are suitable for the relatively slow reconfiguration of current transparent photonic switch technology. The advantage of including both optics and electronics implementation is that packets do not contend over resources, such as shared buses, that are not fundamental to a packet switch. The FBP algorithm is used to change the configuration of the optical centre stage to provide the bandwidth required by the incoming traffic. The switching performance generally constrains by either the data rate or the total port number of the switch. This thesis will then examine the mapping of FBP onto an Agile All-Photonic Network (AAPN). AAPN proposes an overlaid-star topology with edge-nodes interconnected by the beams of the stars via the core switches located at the hub of each star. The Adaptive Wavelength-Timeslot Allocation (AWTA) algorithm is introduced for the network to adapt the configuration of a core node to meet the demands of changing traffic patterns. If the algorithm is used over more than one core node, it may also provide an option to the edge nodes to choose distinct routes with different propagation delays, which can relieve the routing of delay-critical traffic. The results show that the queuing delay performance is directly proportional to the time between configurations of the core node and the links propagation delays.
Keywords: Engineering, Electronics and Electrical.